Pengaruh Religiusitas, Budaya, Pengetahuan Terhadap Minat Masyarakat Menabung di Koperasi Syariah - Suprihati Suprihati; Sumadi Sumadi; Muhammad Tho'in (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this study was to determine the influence of cultural religiosity and knowledge on public interest in Islamic cooperatives. Methods of data study through direct observation with questionnaires, interviews with people who save at the Bina Insan Mandiri Sharia Cooperative as the population and the sample. This study uses multiple linear regression with classical assumption and hypothesis testing. The results of this study found that religiosity has no significant effect on people's interest in saving in Islamic cooperatives, culture has a significant effect on people's interest in saving in Islamic cooperatives. knowledge does not have a significant effect on people's interest in saving in Islamic cooperatives. Simultaneously there is an influence between religiosity, culture and knowledge on people's interest in saving in Islamic cooperatives.